Does canopy nitrogen uptake enhance carbon sequestration by trees?. (14th December 2015) - Nair, Richard K. F.; Perks, Micheal P.; Weatherall, Andrew; Baggs, Elizabeth M.; Mencuccini, Maurizio
Abstract: Temperate forest 15 N isotope trace experiments find nitrogen (N) addition‐driven carbon (C) uptake is modest as little additional N is acquired by trees; however, several correlations of ambient N deposition against forest productivity imply a greater effect of atmospheric nitrogen deposition than these studies. We asked whether N deposition experiments adequately represent all processes found in ambient conditions. In particular, experiments typically apply 15 N to directly to forest floors, assuming uptake of nitrogen intercepted by canopies (CNU) is minimal. Additionally, conventional 15 N additions typically trace mineral 15 N additions rather than litter N recycling and may increase total N inputs above ambient levels. To test the importance of CNU and recycled N to tree nutrition, we conducted a mesocosm experiment, applying 54 g N/ 15 N ha −1 yr −1 to Sitka spruce saplings. We compared tree and soil 15 N recovery among treatments where enrichment was due to either (1) a 15 N‐enriched litter layer, or mineral 15 N additions to (2) the soil or (3) the canopy. We found that 60% of 15 N applied to the canopy was recovered above ground (in needles, stem and branches) while only 21% of 15 N applied to the soil was found in these pools. 15 N recovery from litter was low and highly variable. 15 N partitioning among biomass pools and age classes also differed among treatments, with twice as much 15 N found in woody biomass when deposited on the canopy than soil. Stoichiometrically calculated N effect on C uptake from 15 N applied to the soil, scaled to real‐world conditions, was 43 kg C kg N −1, similar to manipulation studies. The effect from the canopy treatment was 114 kg C kg N −1 . Canopy treatments may be critical to accurately represent N deposition in the field and may address the discrepancy between manipulative and correlative studies.